Produção de substâncias bioativas por microrganismos endofíticos isolados do Cerrado de São Carlos-SP - Favoretto, Naira Beatriz (Universidade Federal de São Carlos, 2010)
The Brazilian tropical savannah occupies a large area in Brazil and includes a high variety of plant species. This diversity is an important source of endophytic microorganisms consisting mainly of bacteria and fungi that inhabit the interior of plants. Endophytes can produce bioactive metabolites that exhibit activities of biotechnological interest, such as antibacterial and antifungal action. The aim of this study was to isolate from Butia capitata var capitata (Coquinho-do-cerrado), Solanum lycocarpum (Lobeira), Stryphnodendron polyphyllu (Barbatimão), Miconia albicans (Quaresmeira-white) and Aegiphila lhotzliana (Tamanqueira), collected on Brazilian tropical savannah at São Carlos, SP, endophytic microorganisms with suggestive features of the genus Streptomyces. The samples were characterized through macroscopic, physiological, biochemical and morph-dying characteristics. The antagonistic potential was tested against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Serratia marcensis ITB 1475, Enterococcus faecalis ATCC 29212, Shigella sonnei ATCC 10231 and Candida albicans ATCC 10231. 26 samples of endophytic microorganisms were isolated and selected two, one from Butia capitata var capitata and another one from Miconia albicans. Both presented microbiological characteristics of Streptomyces. The microorganism isolated from Butia inhibited the growth of Staphylococcus aureus (13 mm) and Enterococcus faecalis (11 mm), and the one isolated from Miconia did not show bioactivity against the pathogens tested.
Keywords: Biotecnologia; Microbiologia; Microorganismos endofíticos; Antimicrobiana; Cerrado; Streptomyces; Substâncias bioativas; Brazilian tropical savannah; Bioactive substances; endophytes; Streptomyces; CIENCIAS BIOLOGICAS::MICROBIOLOGIA